Рекомендация дифференциальных уравнений движения вязкопластичных неньютоновских эмульсионных смесей - Аванесян, В. Г.
To recomment differential eguations of the motion of visco -plastic emulsive mixture in the form of Henky-llushin in cartesian coordinates, in vector- tensor form and in the form of Lamba, as well a s to introduce the experessions for definition of normal and tangent tension of the same mixture.
Keywords: Механика